Regulación de comisiones de cajero en un modelo de competencia espacial - Karen Kaiser; Carlos Lever (Banco de México, 2011)
– Following the Hotelling model of spatial competition used by Massoud and Bernhardt (2002) to analyze competition in ATM fees, in this paper we analyze the effects of banning fees on the usage of ATMs by account holders. We find that the prohibition also reduces the fees charged to non-account holders but increases fixed fees. This latter increase is on average smaller than the decrease of the former two, which leads total consumer welfare to increase. We also find that the prohibition decreases total surplus but that this decrease is absorbed by the banks' profits. The model does not consider the decision of banks to open or closedown ATMs, which we leave for future research.
Keywords: G21; L51; D40; 330; banking competition; ATM fees; bank regulation; retail banking; Electronic Banking; Bankentgelt; Bankenregulierung; Privatkundengeschäft; Räumlicher Wettbewerb; Mexiko